Kościół i klasztor bernardynów w Radomiu od XV do XVIII w. Miejsce działalności społecznej i stały element krajobrazu miejskiego - Janicka, Anna (Acta Universitatis Lodziensis. Folia Historica, 2010)
The article discusses particular phases of building establishment of OO. Bemardine’s churchmonastery in Radom, putting them between many other medieval foundations of this congregation. The analysis gives typical for medieval Bernardine view of establishment creating the quadrilateral with viridary in the middle and church situated from the north and farm buildings perpendicularly adjoining to south wing of monastery. Simultaneously, article shows the church and monastery as the place which mattered (featured) a lot in local community’s life. Just the enclosing of the building with the battlements in 1500 year made it a place of shelter in case of danger for the population living in the suburbs. The Bemardine’s assembly from the one hand provided the pastoral and religious service, but on the other hand they involved the local community into such activities as collection, guilds which all became the active element of church-monastic life. Bemardine’s church and monastery, although it was built with a view of poor community living in the suburbs, became also significant centre of religious life among rural community and also a place of meetings of the parliament, meetings of Revenue Tribunal, and the centre of active political life. The institution stayed for good also in the history of Poland.